Design recommendations for XR-based motor rehabilitation exergames at home - Lorenz, Emanuel A.; Bråten Støen, Andreas; Lie Fridheim, Magnus; Alsos, Ole Andreas (Frontiers in Virtual Reality, 2024)
Introduction: Acquired brain injuries pose significant societal and individual challenges worldwide. The adoption of XR technologies presents an opportunity to enhance current rehabilitation procedures. However, a comprehensive understanding of the specific requirements of different user groups in XR-based rehabilitation remains incomplete. Our objective was to identify design recommendations for designers and researchers of XR-based exergames for motor rehabilitation for lower-limb motor recovery at home. Methods: After initially conducting a mini-literature review and brief market analysis, we used a human-centered design process, interviewing central stakeholders to understand their perspectives and using thematic analysis to identify recurring themes and insights related to XR-based rehabilitation. Results: The resulting eight key themes for integrating XR-based exergames into acquired brain injuries (ABI) rehabilitation were safety, flexibility, efficacy, usability, technology, motivation, ownership, and social factors. Conclusion: By addressing technical and user-oriented demands, our resulting design recommendations aid designers in developing meaningful XR-based rehabilitation exercises.